FRI0266 Health-Related Quality of Life of Patients with Rheumatoid Arthritis Achieving DAS28 Remission, Improvement in Physical Function and NO Radiographic Progression after Treatment with Intravenous Golimumab. (10th June 2014) - Westhovens, R.; Weinblatt, M.E.; Han, C.; Kim, L.; Mack, M.; Lu, J.; Baker, D.; Mendelsohn, A.; Bingham, C.O.
Abstract : Objectives: To evaluate "comprehensive remission" in patients with rheumatoid arthritis (RA) treated with intravenously administered golimumab (GLM) and the association with normalized health related quality of life (HRQOL). Methods: GO-FURTHER was a multicenter, randomized, placebo-controlled study. Adult patients with active RA despite MTX therapy (≥6 tender and swollen joints, CRP ≥1.0 mg/dL, and RF and/or anti-CCP positive) were randomized to placebo (PBO) + MTX or GLM (2mg/kg) plus MTX at week 0, 2, and every 8 week thereafter (GLM group). Patients in PBO group with <10% improvement in tender and swollen joint count from baseline at week 16 entered early escape (EE) and received a 2 mg/kg GLM infusion at weeks 16 and 20 and every 8 weeks subsequent. HRQOL was assessed using Short-Form of 36 items questionnaire (SF-36) and FACIT-fatigue. Employability was defined as being employed or to be able to work if job is available. Radiographic progression was measured using Total Sharp score (TSS). "Comprehensive remission" was defined as achieving low disease activity score (DAS28 using CRP <2.6), normalized physical function (HAQ-DI≤0.5) and no radiographic progression (change in TSS ≤ Smallest detectable change). Remission was also assessed using criteria of Simplified Disease Activity Index (SDAI, ≤3.3). Results: Compared to PBO+MTX group at week 24, greater proportion of patients in GLM IV group achieved DAS28<2.6 (17.7% vs. 5.1%, p<0.001), HAQ-DI score≤0.5 (29.4% vs. 16.2%, p<0.001) or no radiographic progression (91.4% vs. 80.7%, p<0.001). "Comprehensive remission" rate was 10.1% in GLM group vs. 2.5% in PBO+MTX group (p=0.001). Additionally, SDAI remission at week 24 was 7.6% in GLM group vs. 2.0% in PBO+MTX group (P<0.01)."Comprehensive remission" was sustained in the GLM group over time at week 52 (12.4%) or week 100-112 (15.4%). Compared to patients who achieved DAS28 remission or SDAI remission, patients who achieved "comprehensive remission" at week 24 achieved numerically greater improvement in normalized HRQOL in SF-36 PCS and MCS and in FACIT-fatigue, and were more likely regain employability at Week 24, 52 or week 112. Conclusions: By taking into consideration of outcomes reported by clinician and patient, and radiographic progression, "comprehensive remission" might be a more desirable treatment goal for patients with RA. Disclosure of Interest: R. Westhovens Grant/research support: Janssen R & D, LLC, M. Weinblatt Grant/research support: Janssen R & D, LLC, C. Han Employee of: Janssen Pharmaceutical Services, LLC, L. Kim Employee of: Janssen R & D, LLC, M. Mack Employee of: Janssen R & D, LLC, J. Lu Employee of: Janssen R & D, LLC, D. Baker Employee of: Janssen R & D, LLC, A. Mendelsohn Employee of: Janssen R & D, LLC, C. Bingham III Grant/research support: Janssen R & D, LLC, Consultant for: Janssen R & D, LLC DOI: 10.1136/annrheumdis-2014-eular.3819